SELECTION OF CROSSING FACILITIES BASED ON CRITICAL GAP (CASE STUDY DHARMAWANGSA STREET, SURABAYA) - Edwin Hidayat (Widyariset, 2012)
Pedestrians have a high risk to be hit by motor vehicle when they crossed the street, thus the choose ofappropriate cross facilities are very important. An alternative for choosing cross facilities are by using the CriticalGap method. This method is used to measure the possibility of crossing the street safely. This study was startedby gathering primary data for 4 hours at the traffic peak hours. From the calculation, the case of DharmawangsaStreet, Surabaya, showed that the critical gap is about 3,55 seconds. The observation from 07.00-11.00 a.m.showed that the possibilities of crossing the road respectively are: 45, 55, 56, and 60. Compared to the numberpedestrians crossing the road, the research showed about 71, 24, 33, and 49 peoples. In this case, the possibility ofcrossing the street at 07.00-08.00 a.m. cannot be fulfilled. Meanwhile, the possibility to cross the street with safelyat 08.00-11.00 a.m. can be fulfilled. Therefore, the use of midblock crosses is still relevant.